2021
DOI: 10.3390/met11111728
|View full text |Cite
|
Sign up to set email alerts
|

Joining Ti6Al4V to Alumina by Diffusion Bonding Using Titanium Interlayers

Abstract: This work aims to investigate the joining of Ti6Al4V alloy to alumina by diffusion bonding using titanium interlayers: thin films (1 µm) and commercial titanium foils (5 µm). The Ti thin films were deposited by magnetron sputtering onto alumina. The joints were processed at 900, 950, and 1000 °C, dwell time of 10 and 60 min, under contact pressure. Experiments without interlayer were performed for comparison purposes. Microstructural characterization of the interfaces was conducted by optical microscopy (OM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…These periods were selected based on the reactivity of Ni/Ti multilayers and on previous dissimilar joining of metallic materials by diffusion bonding [31,34]. A deposition time of ~30 min was selected for a total thickness close to 2.5-3.0 µ m. Titanium's bottom nanolayer ensured a good adhesion to the base materials [24]. Adhesion between Ni/Ti thin films and substrate is particularly relevant for the Al2O3 base material because the lack of adhesion can compromise the diffusion bonding process.…”
Section: Deposition Of Ni/ti Nanomultilayer Thin Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…These periods were selected based on the reactivity of Ni/Ti multilayers and on previous dissimilar joining of metallic materials by diffusion bonding [31,34]. A deposition time of ~30 min was selected for a total thickness close to 2.5-3.0 µ m. Titanium's bottom nanolayer ensured a good adhesion to the base materials [24]. Adhesion between Ni/Ti thin films and substrate is particularly relevant for the Al2O3 base material because the lack of adhesion can compromise the diffusion bonding process.…”
Section: Deposition Of Ni/ti Nanomultilayer Thin Filmsmentioning
confidence: 99%
“…However, the conventional diffusion bonding process involves high temperature, pressure, and dwell time which causes thermal stress due to a mismatch in coefficient of thermal expansion (CTE) and thermal conductivity; consequently, cracks come up at the joint's interface, mainly during cooling [1]. Thus, several approaches have been developed to join dissimilar materials by diffusion bonding, like applying interlayers between the base materials to be joined [17][18][19][20][21][22][23][24]. The interlayer has a crucial role in reducing the temperature and pressure of the bonding process, and consequently, the thermal stress, besides increasing the contact area that favors achieving high strength joints.…”
Section: Introductionmentioning
confidence: 99%
“…Solid-state diffusion bonding is one of the most common joining processes reported in the literature when creating joints between titanium alloys and advanced ceramic materials. However, in these studies it is observed that achieving joint integrity is only possible with high pressures at elevated temperatures [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The drawbacks of this process are primarily associated with economic concerns, due not only to the required equipment but also the processing of the joints and preparation of the base materials.…”
Section: Introductionmentioning
confidence: 99%
“…The use of thin films or multilayers as an interlayer has been demonstrated as a viable approach in bonding Ti6Al4V to Al 2 O 3 through diffusion bonding [9][10][11][12]. This application is attributed to the potential for enhancing diffusivity across the interface, thereby reducing processing conditions, decreasing residual stresses, and improving joint integrity.…”
Section: Introductionmentioning
confidence: 99%
“…The surface exposure and the pressure affect the welding strength [11]. Diffusion bonding was also tested at high temperatures [12][13][14]. Severe plastic deformation breaks the thin brittle oxide surface layer to press the newly created surface under high pressure.…”
Section: Introductionmentioning
confidence: 99%